EFFECT OF ORGANIC FERTILIZERS AND NUTRIENTS ON ANATOMICAL TRAITS OF RED BEETROOTS - Rawaa G. Al-Hlfie; Wafaa A. Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was conducted during fall season 2021-2022 In order to study the effect of soil as an agricultural medium, organic fertilizers (Vermecompost, cow manure) and foliar spraying of silicon and calcium on skin, bark and cambium ring thickness of three beetroot varieties (Red, Dark Red, and Cylindra). Seeds directly sown in the fields of Station A College of Agricultural Engineering Sciences - University of Baghdad - Al-Jadriya campus- Within RCBD a split-plot experiment, where the cultivars were the main unites, organic fertilizer, and foliar spray as the subunits, with three replicates, the number of treatments was 27. The results revealed that the triple interaction treatment of Dark Red, Vermicompost, and silicon spray V2S2F1 was superior in epidermis thickness, cortex thickness, and cambium ring thickness (55.00 μm, 78.90 μm, and 182.07μm) respectively, compared with Cylindra cultivar, soil medium, and spraying with distilled water V3S1F0, which produced the lowest averages (21.77 μm, 31.23 μm, 64.57 μm) respectively. The interaction treatment between Red cultivar, cow manure and spraying with distilled water V1S3F0 excelled in the thickness of the middle xylem ring ( 261.33 μm). Compared with the thinnest middle xylem (143.8 μm) in red cultivar roots treated with soil medium and distilled water.